A novel fusion gene involving PDGFRB and GCC2 in a chronic eosinophilic leukemia patient harboring t(2;5)(q37;q31). Issue 4 (29th January 2019) - Iriyama, Noriyoshi; Takahashi, Hiromichi; Naruse, Hiromu; Miura, Katsuhiro; Uchino, Yoshihito; Nakagawa, Masaru; Iizuka, Kazuhide; Hamada, Takashi; Hatta, Yoshihiro; Nakayama, Tomohiro; Takei, Masami
Abstract: Background: Platelet‐derived growth factor receptor beta ( PDGFRB ) rearrangement has been reported in a number of patients with chronic eosinophilic leukemia (CEL), B‐acute lymphoblastic leukemia, myeloproliferative neoplasms, and juvenile myelomonocytic leukemia. Here, we report a case of CEL carrying a novel fusion gene involving PDGFRB and GRIP and coiled‐coil domain containing 2 ( GCC2 ). Patient and methods: A 54‐year‐old man presenting with a cough and dyspnea was diagnosed with acute eosinophilic pneumonia. Cytogenetic analysis of the bone marrow revealed the presence of t(2;5)(q37;q31). Fluorescence in situ hybridization analysis in the peripheral blood leukocytes revealed the presence of a split signal at PDGFRB gene. Imatinib treatment was effective, and disappearance of t(2;5)(q37;q31) in the bone marrow was confirmed after three months of imatinib therapy. Whole‐genome sequencing was performed in peripheral blood leukocytes collected before imatinib therapy. Results: A novel fusion gene between exon 22 of GCC2 and exon 12 of PDGFRB was detected and the presence of GCC2‐PDGFRB was confirmed by PCR. Conclusion: This is the first case report demonstrating the GCC2 gene as a partner of PDGFRB in the pathogenesis of CEL. Abstract : Whole genome sequence identifying the breakpoint forming platelet‐derived growth factor receptor beta (PDGFRB) and GRIP And Coiled‐Coil Domain Containing 2 (GCC2) fusion gene (a). Direct sequencing analysis confirming the presence of GCC2‐PDGFRB fusion gene (b).